Exploring the Possibility of Running an Electric Locomotive with Cold Nuclear Fusion by Considering Iron‑56 or Magnesium‑24 as Nuclear Fuels - Utpala Venkata, Satya Seshavatharam; Lakshminarayana, Sreerama (New Energy Exploitation and Application, 2025)
In our recently published papers, we have proposed a clear‑cut mechanism for understanding and implementing cold nuclear fusion technology pertaining to fusion of hydrogen with medium and heavy metals. In this contribution, we are making an attempt to understand the possibility of running a locomotive with cold nuclear fusion technology. We are conϐident to say that Iron‑56 and Magnesium‑24 can be considered as cold nuclear fuels operating at a temperature range of 500 to 1500 °C. In this context, we would like to stress the point that, cold nuclear fusion can be considered as the next stage of metallic hydrides and cold fusion of hydrogen can be understood as a phenomenon of weak interaction fusing neutron to the nucleus of the base atom and fusing electron to the electronic orbits of the base atom. With reference to the maximum binding energy per nucleon, liberated safe and controllable thermal energy can be estimated with a simple relation of the form, [8.8–(BE2–BE1)] MeV, where BE1 and BE2 are the nuclear binding energies of initial and ϐinal atomic nuclides. It is the order of (1 to 3) MeV per atom against 200 MeV pertaining to the dangerous and unsafe nuclear ϐission of one Uranium atom. As the whole world is having a huge scarcity of electric power and severe environmental pollution issues, our proposal can be given a chance. It needs funding for conducting long run experiments and pilot projects.